Industrial training presentation: Telekom Malaysia Technology Services / Muhammad Shahmirul Fahmi Supian - Supian, Muhammad Shahmirul Fahmi (Faculty of Business and Management, 2023)
This report is about my internship program at Telekom Malaysia Technology Services (TM Tech). In this report, I have discussed SWOT Analysis of TM Tech which I observed and perceived during my internship program. In this report you will find the details about TM Tech about their company establishment, and services that they offered. Along with it, the processes, vision and mission of the company are also discussed in detail. During my internship program, I mainly worked under the Small Medium Enterprises (SME) department. The main purpose of the internship is to learn by working in a practical environment and to apply the knowledge acquired during the studies in a real-world scenario in order to tackle the problem using the knowledge and skill learned during the academic process. The report includes a comprehensive SWOT analysis of TM Tech, a subsidiary of TM that focuses on providing technology solutions. This analysis evaluates TM Tech’s strengths, weaknesses, opportunities, and threats, which can guide strategic decision-making and further strengthen TM Tech's position in the market. This industrial training report covers many important aspects which are basically related with the operations of the company. The end of the learning and experiences section consists of all information about the company, my experiences during internship, benefit and allowance, skills and knowledge I gained through industrial training at TM Tech, discussion of SWOT Analysis and recommendation for each SWOT.